Impact De Microcredit Sur Le Bien-Etre Des Menages De La Ville De Kenge (International Journal of Scientific Research and Management (IJSRM), 2024)
The main concern in this investigation is to analyze the impact of access to microcredit on improving thewell-being of households in the city of Kenge. Specifically, the first step is to identify the determinants ofaccess to microcredit at the COOPEC; Secondly, it is a question of determining the effect of the treatment(access to micro-credit) on the well-being of the beneficiaries’ households. To carry out our study, the dataof this study were collected in a blind (accidental) sample of 260 individuals drawn from a population of3.591 members of the Mutual Woman and Man evolve together for the Development of the KwangoMFHPEK. Multiple regression with the Logit model used to identify the determinants of access tomicrocredit and the evaluation of the effects of treatment with the propensity score matching method. The results of the logit regression reveal that gender, socio-professional category (categories employees withsalary or civil servant and trader), having access to a support service are positively associated with thepropensity to access credit at the COOPEC at the 1% threshold. On the other hand, the distance from thelocal market negatively influences the fact of receiving credit at the COOPEC at the 5% threshold. As forthe propensity score matching method, receiving credit positively improves the beneficiary’s schooling rate.On the other hand, a negative impact is observed on income as well as food consumption